The Influence of Transformational Leadership and Workload towards Work Motivation and Their Impact on Employee Performance at Bank BRI Tenggarong Branch - Taqwa, Syukur; Hudayah, Syarifah; Lestari, Dirga (Budapest International Research and Critics University, 2021)
The high level of competition in the banking industry makes human resources must work in the best way. In order to improve the quality of human resources, Bank Rakyat Indonesia (BRI) Tenggarong branch has a performance management system (SMK) designed to evaluate employee performance. The leadership factor plays an important role, because it plays a role in advancing and guiding to achieve company goals. The workload factor is an aspect that must be considered because it can affect employee work productivity, as well as employee motivation factors as a driver of employee behavior in doing work. The performance of employees at BRI Tenggarong branch is currently experiencing a decline in performance compared to the previous year. The population in this study were permanent employees at the Tenggarong branch of BRI bank with a total sample of 96 respondents. In this study using descriptive analysis to determine the characteristics of the respondents' responses with purposive sampling method which aims to determine several criteria for the sample of respondents to employees. In the analysis of data processing, the structural equation modeling–partial least square (SEM-PLS) program was used to predict the model relationship between the variables and indicators studied. The results of this study indicate that transformational leadership has a significant positive effect on work motivation; transformational leadership has a significant positive effect on employee performance; workload has a significant positive effect on work motivation; workload is not significant and has a negative effect on employee performance; and work motivation significantly positive effect on employee performance.